Mental health literacy and resilience as predictors of psychological well-being among university students: The mediating role of perceived social support - Rahma, Ulifa (Psikoislamika: Jurnal Psikologi Islam, 2025)
This study aimed to examine the role of mental health literacy (MHL) and resilience in predicting psychological well-being (PWB) among university students, with perceived social support (PSS) as a mediating factor. A quantitative correlational design with mediation analysis was employed, involving 600 undergraduate students recruited through purposive sampling. Data were collected using validated self-report instruments, namely the Mental Health Literacy Questionnaire for Young Adults (MHLq), the Connor–Davidson Resilience Scale (CD-RISC), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Psychological Well-Being Scale (PWB). Mediation modeling was conducted in JASP using linear regression and bootstrapped indirect effect testing. The results showed that both MHL and resilience significantly and positively predicted PWB, with resilience emerging as the stronger predictor. Moreover, PSS partially mediated the relationships between both predictors and PWB, although the indirect effect of MHL through PSS was relatively small. These findings highlight the importance of integrating psychoeducation on mental health literacy with resilience training and peer support systems in higher education. Theoretically, this study enriches the positive psychology framework by demonstrating the interplay between internal strengths and external supports in fostering student well-being. Keywords: mental health literacy; resilience; psychological well-being; social support; university students